Association of Triglyceride/High Density Lipoprotein Cholesterol Ratio and Coronary Lesion Severity in Acute Myocardial Infarction Patients at Adam Malik Hospital, Medan - Sinaga, Akbar; Hasan, Refli; Reynaldo, Abdul Halim; Hasan, Harris; Akbar, Nizam Zikri; Andra, Cut Aryfa (Journal of Society Medicine, 2023)
Introduction: Coronary heart disease is the leading cause of worldwide death. A number of markers have been identified in terms of the atherogenic potential of the lipid profile.The TG/HDL-C ratio is an easy and economical non-invasive examination method as a predictor of coronary heart disease severity. The aim of this study is to assess the relationship of the TG/HDL ratio with the severity of coronary lesions. Method: This cross-sectional study included 53 acute myocardial infarction patients undergoing coronary angiography. Exclusion criteria include (1)AMI patients receiving fibrinolytic therapy, (2) Patients who have routinely consumed lipid lowering drug for 6 weeks,(3) Incomplete coronary angiography and medical records. The TG/HDL ratio is the result of dividing the triglyceride value by HDL. The TG/HDL ratio was divided into 2 groups, namely the TG/HDL ratio <4 group and the TG/HDL ratio >4 group. The severity of coronary lesions was described by the SYNTAX score, which was divided into two: the low SYNTAX score group (≤22) and patients with a low SYNTAX score (≤22) and medium-high SYNTAX score (≥23). Bivariate analysis was performed to find the relationship between the TG/HDL ratio and the SYNTAX score. The value of p<0.05 was considered statistically significant. Results: From 53 patients, 26 patients (49.1%) had a SYNTAX score ≥ 23 and 27 patients (50.9%) had a SYNTAX score < 23. Patients with NSTEMI, DM risk factors, and obesity were higher in the SYNTAX score group ≥23. From the results of statistical analysis, there was a significant relationship between the TG/HDL ratio with coronary lesion severity (p = 0,004). Conclusion: Enhancement of TG/HDL ratio is correlated with coronary lesion severity in acute myocardial infarction patients using the SYNTAX score.